Optimalisasi Pemanfaatan Smartphone dalam Pembuatan Foto Produk Cenderamata di Desa Tanjung Selamat, Aceh Besar - Lindawati; Alaisyi; Zamakhari, Ahmad; Silviana, Mery; Wardani, Sari; Sari, Dewi Maya (Jurnal Pengabdian Nasional (JPN) Indonesia, 2024)
The advancement of information technology has significantly driven developments in business and marketing. Marketing processes that were previously conducted conventionally have now transitioned to digital marketing models. Many products produced by business actors are of good quality but often fail to sell due to their inability to compete in the online market. One contributing factor is the suboptimal promotion of products, particularly in terms of unattractive product photos. To address this issue, training aimed at enhancing skills in product photography is necessary. Mastery of information technology is crucial to support and improve business processes. This community service activity aims to equip prospective souvenir entrepreneurs with the skills to photograph and edit products attractively, enabling them to compete in the online market. The training method provided includes lectures, practical training, and guidance on creating product photos simply, quickly, and easily using smartphone devices for the PKK mothers in Tanjung Selamat Village, Aceh Besar. The results of this training demonstrate that participants are able to apply the skills acquired to develop souvenir businesses by producing attractive product photos for promotion, thereby increasing consumer interest and encouraging product purchases through promotional media such as leaflets, brochures, or product packaging